Utilization of Plastic Waste as a Creative Learning Media to Improve Literacy and Numeracy for Early Childhood: Pemanfaatan Sampah Plastik sebagai Media Pembelajaran Kreatif untuk Meningkatkan Literasi dan Numerasi bagi Anak Usia Dini - Farissi Hamama, Syarifah; Irma Aryani; Maulida, Maulida; Nurul Nisa; Nurul Qolbiya (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
TK Karyawan Kota Baru is a private Kindergarten located in a school and office complex, so the amount of plastic waste in the environment around the Kindergarten is very high. Plastic waste in the school environment has not been managed well. Moreover, student interest in literacy and numeracy at this school is still relatively low, especially among students aged 4 years. This activity focuses on increasing the knowledge of 11 partners regarding the impact of plastic waste on the environment, increasing creativity in reprocessing plastic waste (recycling) into interactive learning media, and improving students' (early childhood) literacy and numeracy skills at TK Karyawan Kota Baru. The methods used in this service are socialization regarding plastic waste, training in creating interactive media using Canva-Pro, and mentoring and evaluation. Through this activity, partners gain knowledge related to plastic waste processing and produce interactive media to improve students' (early childhood) literacy and numeracy skills.